Pengaruh Citra Merek, Kepercayaan Merek, dan Desain Produk Terhadap Keputusan Pembelian Konsumen pada Handphone Vivo di Yogyakarta - Azam Fajrul Faizy; Muinah Fadhilah; Nonik Kusuma Ningrum (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract The growth in cellular usage is very rapid, and of course, this is an opportunity for smartphone or smart cellular business people. Smartphone or smart cellphone manufacturers are required to continue to innovate and develop their products so that they are in demand by the public. This study aims to determine the effect of brand image, brand trust, and product design on purchasing decisions among Vivo cellphone consumers in the city of Yogyakarta. A sample of 100 respondents was taken using a purposive sampling technique. Data were collected by questionnaire as a data collection method. The data analysis techniques used are quantitative descriptive analysis, prerequisite analysis test, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of this study are: Brand image, brand trust, and product design both partially and simultaneously have a positive and significant effect on purchase decisions for Vivo Mobile consumers in Yogyakarta City.. Keywords: Brand Image, Brand Trust, Product Design, Purchase Decision. Abstrak Pertumbuhan penggunaan seluler sangat pesat, tentunya menjadi peluang bagi pelaku bisnis Smartphone atau seluler pintar. Produsen Smartphone atau seluler pintar dituntut untuk terus berinovasi dan mengembangkan produknya, sehingga diminati oleh masyarakat. Penelitian ini bertujuan untuk mengetahui Pengaruh Citra Merek, Kepercayaan Merek serta Desain Produk terhadap Keputusan Pembelian pada Konsumen Handphone Vivo di Kota Yogyakarta.Sampel diambil sebanyak 100 responden dengan menggunakan teknik purposive sampling. Data dikumpulkan dengan kuesioner sebagai metode pengambilan data. Teknik Analisis data yang digunakan adalah Analisis Deskriptif Kuantitaif, Uji Prasyarat Analisis, Analisis Regresi Linier Berganda, Uji Hipotesis, dan Koefisien Determinasi. Hasil dari penelitian ini adalah : Citra Merek, Kepercayaan Merek serta Desain Produk baik secara parsial maupun simultan berpengaruh positif dan signifikan terhadap Keputusan Pembelian pada Konsumen Handphone Vivo di Kota Yogyakarta Kata Kunci: Citra Merek, Kepercayaan Merek, Desain Produk, Keputusan Pembelian. Handphone